Serum adiponectin and resistin in relation to insulin resistance and markers of hyperandrogenism in lean and obese women with polycystic ovary syndrome - Olszanecka-Glinianowicz, Magdalena; Kuglin, Dorota; Dąbkowska-Huć, Anna; Skałba, Piotr (European journal of obstetrics & gynecology and reproductive biology, 2011)
It seems that adipokines participate in disturbances of the function of the hypothalamus–pituitary–ovary axis. The aim of the study was to assess the relationship between plasma adiponectin and resistin levels and insulin resistance and markers of hyperandrogenism in lean and obese PCOS women. Forty-one women with PCOS (22 lean and 19 obese) and 16 healthy lean women were enrolled. Body mass and height were measured and body mass index was calculated. In addition to serum glucose, lipids, androgens and insulin, adiponectin and resistin concentration were assessed in the fasting state. The insulin resistance was calculated based on the HOMA-IR. Similar serum resistin concentrations were found in both PCOS subgroups and controls. The obese PCOS subgroup was characterized by the lowest serum adiponectin level (10.8 ± 8.3, compared with 21.0 ± 15.1 in the normal weight PCOS subgroup and 26.7 ± 12.5 μg/ml in controls). There were no correlations between resistin and adiponectin levels and HOMA-IR values and serum androgen concentrations. Significant positive correlations between adiponectin to resistin ratio and plasma FSH ( r = 0.49; p = 0.001) and LH ( r = 0.45; p = 0.003) concentrations, and a negative correlation with free androgen index ( r = −0.34; p = 0.03) in PCOS group were found. Obese but not normal weight PCOS women have lower adiponectin levels whereas resistin concentration did not differ in normal weight and obese PCOS compared to control subjects. We hypothesize that changes of the relative proportion of adiponectin to resistin, but not circulating adiponectin and resistin levels themselves, may play a role in hormonal disturbances but not in insulin resistance in PCOS.